'They Gave Me Nothing': Marriage, Slavery and Divorce in Twentieth-Century Abeokuta. (3rd April 2022) - Asaaju, Morenikeji
ABSTRACT: During the early twentieth century, several hundred women in colonial Abeokuta initiated divorce proceedings against their husbands, who were also frequently their masters. The legal records associated with their cases offer important clues about how women – both freeborn and slave – contested the terms of their marriages using the colonial courts. This article examines how and why these women used new interpretations of marriage, which were introduced by European Christian missionaries and the British colonial administrators in order to challenge established traditions. It reveals how colonial native courts approached indigenous norms surrounding marriage and slavery: colonial interventions gave freeborn women a measure of agency within marriage which was also somewhat unexpectedly extended to slave wives. Through an exploration of court judgements, this article demonstrates the effects of colonial intervention on marriage and slavery and the role of the colonial courts in local matrimonial disputes and practices and investigates how they empowered enslaved wives.